Open pit mine planning considering geomechanical fundamentals. Issue 4 (19th May 2018) - Parra, Andrés; Morales, Nelson; Vallejos, Javier; Nguyen, Phu Minh Vuong
Abstract: The objective of this study is to integrate the admissible factor of safety (FoS) into the mine planning. The analysis showed, as expected, that a lower net present value (NPV) is obtained with the increase in the admissible FoS. Most importantly, it demonstrated that the FoS of the slopes of the adjacent phases, which are not part of the final pit, are considerably greater than the admissible FoS. Therefore, the NPV of an open pit mine project can be increased by steepening the slopes of adjacent phases that are not part of the final pit walls.